LANGUAGE AND CULTURE - Azizova Moxinur Muzaffarjon kizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In article Language is one of the most important parts of any culture. Language is intrinsic to the expression of culture. As a means of communicating values, beliefs and customs, it has an important social function and fosters feelings of group identity and solidarity. It is the means by which culture and its traditions and shared values may be conveyed and preserved.